Pendekatan STEM Dalam Meningkatkan Kreativitas Pembelajaran Ilmu Geografi Bagi Peserta Didik - Iqbal, Muhamad; Sri Murtiasih (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
One of the concepts that need to be mastered by students at the high school level is the concept of solving a problem in learning geography. However, in fact, for the case of students at SMA Widya Nusantara Bekasi, especially in class X IPS 1, many still have difficulty in designing concepts in solving problems in learning geography, making it difficult for students to develop their creativity in solving problems in learning geography. This study is intended to stimulate students' creativity in solving problems so that they can develop their level of knowledge in learning geography. The method that will be used is to take a STEM (Science, Technology, Engineering, and Mathematics) approach through the PBL (Problem Based Learning) model with qualitative data analysis of interactive models to place students in direct problem situations to be able to be active in finding solutions and think critically. From the model applied, researchers found changes in students' way of thinking in solving problems by conducting group discussions, students become active and exchange ideas in determining solutions in solving problems and can utilize developing technology in solving problems.